Two-dimensional perovskite resistive random access memory device based on ionic liquid solvent and preparation method thereof
By using ionic liquid solvents to prepare two-dimensional perovskite films in an air environment, the problems of complex preparation processes and solvent toxicity in the prior art are solved, and a high-performance non-volatile resistive memory is realized.
Patent Information
- Application Number
- CN202411869943.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, the preparation process of two-dimensional perovskite films is complex and needs to be carried out under a high vacuum environment. The solvent has certain toxicity, which limits the large-scale preparation of perovskite memory.
Two-dimensional perovskite films were prepared using ionic liquid solvents, and BA2PbIx(Ac)4-x films were prepared by mixing PbI2 precursor material with butylamine acetate solvent in an air environment and spin-coated.
The preparation process of perovskite films is simplified, and efficient preparation is achieved in air environments. The film is dense and has high coverage. The device exhibits non-volatile storage characteristics, and the switching ratio reaches 104, with excellent performance.
Smart Images

Figure CN119654037A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor materials and functional devices, and in particular to a two-dimensional perovskite resistive memory device based on an ionic liquid solvent and a preparation method thereof. Background Art
[0002] With the rapid development of artificial intelligence and big data technology, the storage of massive data has continuously increased the data processing capabilities of memory. Traditional non-volatile memories such as floating gate memory and dynamic random access memory have reached their theoretical limits. Therefore, there is an urgent need to develop new non-volatile memories. Resistive random access memory has the advantages of simple structure, high storage density, fast read and write speed, long life and compatibility with complementary metal oxide semiconductor processes, and has been widely applied and studied. Therefore, the development of resistive random access memory devices with stable storage performance and low cost is an important topic in the memory field.
[0003] The materials that can realize the resistive memory function mainly include inorganic materials, organic materials and organic-inorganic hybrid materials. In recent years, organic-inorganic hybrid perovskite materials have been widely used in solar cells and light-emitting diode devices due to their excellent optoelectronic properties. At the same time, this material also has good development prospects and application value in resistive memory. Lee et al. discovered the resistive memory properties based on the two-dimensional perovskite BA2PbBr4 film (ACS Appl. Mater. Interfaces 2019,11, 20225−20231), but the preparation process of perovskite film is complicated and the homogenization preparation is difficult. It is necessary to first evaporate the lead bromide film in a high vacuum environment, and then transfer it to the glove box to use butylamine bromine vapor to realize the perovskite phase transition.
[0004] Chinese invention patent, application publication number CN115332438A, the invention name is "A two-dimensional halogen perovskite resistive random access memory and its preparation method", the patent mentions a preparation method of a two-dimensional perovskite resistive random access memory, but the method uses a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide to prepare perovskite, which generally needs to be prepared in an inert, anhydrous and oxygen-free environment, and the solvent has certain toxicity, which limits the large-scale preparation of perovskite memory.
[0005] Therefore, developing a method for preparing a resistive random access memory that can prepare a two-dimensional perovskite film in an air environment and has a simple preparation process is an important issue in the field of perovskite resistive random access memory. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a two-dimensional perovskite resistive memory device based on ionic liquid solvent and a preparation method thereof, which is a non-volatile resistive memory that can be repeatedly read and written. The preparation process is simple, the switching ratio is high, and the device performance is excellent, which is of great significance for the development of two-dimensional perovskite memory. The device is a typical non-volatile memory that can complete data storage at a lower voltage, and the switching ratio reaches 10 4 , excellent performance.
[0007] In order to solve the technical problem of the present invention, the technical solution is: a two-dimensional perovskite resistive memory device based on ionic liquid solvent, characterized in that: it includes a glass substrate, on which are sequentially a bottom electrode, a two-dimensional perovskite resistive layer and a top electrode; the bottom electrode is a transparent conductive glass ITO; the resistive layer material is BA2PbI x (Ac) 4-x The film; the top electrode is Al; the preparation steps are as follows:
[0008] (1) Cleaning ITO
[0009] First, ultrasonicate the ITO conductive glass in deionized water, acetone, and alcohol for 30 minutes, and then irradiate the ITO surface with ultraviolet light in a UV cleaner for 15 to 20 minutes.
[0010] (2) Preparation of perovskite precursor solution
[0011] Weigh 461 mg (1 mmol) of PbI2, add it to 1 mL of butylamine acetate solvent, place it on a 60°C hot plate and stir overnight to dissolve, and prepare a perovskite precursor solution with a concentration of 1 mol / L;
[0012] (3) Preparation of perovskite thin films
[0013] In an air environment, the ITO substrate in step (1) is heated to 80-90°C, and the perovskite precursor solution in step (2) is measured by a pipette and spin-coated on the ITO surface, the spin coater speed is set to 3000-4000 rpm, the time is 20s, and then annealed at 90-100°C for 5 min to obtain a perovskite film layer;
[0014] (4) Preparation of top electrode
[0015] The substrate in step (3) is placed in a vacuum evaporation device, and a strip array Al electrode with a width of 2.5 mm and a thickness of 100 nm is deposited on the surface of the perovskite film using a vacuum evaporation method and a mask plate to obtain a device with a cross structure.
[0016] Preferably, the bottom electrode is a transparent conductive glass ITO with a thickness of 200 nm, a strip shape and a width of 2 mm; the resistive layer material is BA2PbI x (Ac) 4-x The resistive layer has a thickness of 300 to 350 nm, a rectangular shape, and a side length of 12 mm; the top electrode is Al, has a thickness of 100 nm, and is in the shape of a strip array with a width of 2.5 mm.
[0017] Preferably, in step (4), the width of the deposited film on the surface of the perovskite film is 2.5 mm using a vacuum evaporation method and a mask.
[0018] Preferably, in step (3), the rotation speed of the spin coater is set to 4000 rpm, and the thickness of the resistive layer film obtained is 300 nm.
[0019] Preferably, in step (3), the rotation speed of the spin coater is set to 4000 rpm, and the thickness of the resistive layer film obtained is 300 nm. In step (4), the width of the deposition on the surface of the perovskite film is 2.5 mm using a vacuum evaporation method and a mask.
[0020] Compared with the prior art, the beneficial effects of the present invention are:
[0021] (1) The present invention proposes for the first time a method for preparing a two-dimensional perovskite film by dissolving a precursor material PbI2 in a butylamine acetate solution. The BA2PbI2 film with a dense structure, high film coverage and no voids is prepared by one-step spin coating in air. x (Ac) 4-x The film improved the preparation process of the two-dimensional perovskite film. The device based on the film exhibits non-volatile storage characteristics. The memory can store data at low power consumption, and the storage switching ratio reaches 10 4 . When a forward voltage in the range of 0-0.7 V is applied, the device first exhibits a "high resistance state". When the voltage reaches 0.7 V, the current rises rapidly, indicating that the device changes from a "high resistance state" to a "low resistance state", which is the "write" process of the memory. Subsequently, when the voltage is scanned from 2 V to -2 V, the device changes to a "high resistance state" at a voltage of -0.3 V, realizing a non-volatile resistive memory that can be read and written repeatedly.
[0022] (2) Compared with the traditional two-dimensional perovskite film preparation method, the preparation method of the present invention is simple, using only one precursor material, and the perovskite film can be prepared in an air environment, which solves the problem that the traditional process of preparing perovskite film must add an anti-solvent in a water-free and oxygen-free environment, simplifies the process flow, and has strong operability.
[0023] (3) The surface morphology (SEM) of the perovskite film of Examples 1-4 is shown in Figure 2 As shown. The film coverage formed by low concentration of PbI2 is low, and there are a large number of relatively large pinholes, and the film morphology is poor. As the concentration of PbI2 increases, the overall grain size increases, the pinholes also decrease significantly, and the film coverage gradually increases. At a concentration of 1.3 mol / L, a large amount of PbI2 is instantly precipitated during the annealing process of the film, forming large grains that are disorderly piled up, resulting in an uneven film surface. The perovskite solution with a concentration of 1 mol / L in Example 1 exhibits the best film morphology.
[0024] (4) The X-ray diffraction (XRD) pattern of the perovskite film of Example 1-4 is as follows: Figure 3 As shown. For films with different concentrations, the PbI2 peak is dominant. It is worth noting that as the PbI2 concentration increases, the film shows a gradually enhanced diffraction peak at 2θ≈8.3°. This peak has a certain displacement compared to the traditional two-dimensional BA2PbI4 perovskite diffraction peak. The residual Ac in the film - Entered the PbI2 lattice to form the structure BA2PbI x (Ac) 4-x Perovskite. In the precursor solution, butylamine acetate is wrapped around PbI2, where Ac - It is very easy to form a strong Pb-O bond with PbI2, which can promote the dissolution of PbI2 to form a relatively stable precursor solution. Under annealing conditions, the nucleation process of perovskite is - Pb 2+ Formation of [PbI6] 4- Octahedron. The remaining Ac in the film - Ionic radius and I - are of the same order of magnitude, so Ac - Participate in the formation of [PbI x (Ac - ) 6-x ] 4- , and then form BA2PbI x (Ac) 4-x Perovskite. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the structure of perovskite resistive random access memory.
[0026] Figure 2 Surface morphology (SEM) images of the perovskite films in Examples 1-4 of the present invention.
[0027] Figure 3 1 is an X-ray diffraction (XRD) diagram of the perovskite thin film in Example 1-4 of the present invention.
[0028] Figure 4 FIG. 4 is a graph showing the IV relationship of the memory device in the first embodiment of the present invention.
[0029] Figure 5 4 is an IV relationship curve diagram of the memory device in Comparative Example 1 of the present invention.
[0030] Figure 6 4 is an IV relationship curve diagram of the memory device in Comparative Example 2 of the present invention.
[0031] Figure 7 4 is an IV relationship curve diagram of the memory device in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0032] The following is a detailed description of an embodiment of the present invention in conjunction with the accompanying drawings: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0033] Embodiment 1:
[0034] (1) Cleaning ITO
[0035] First, ultrasonicate the ITO conductive glass in deionized water, acetone, and alcohol for 30 minutes, and then irradiate the ITO surface with ultraviolet light in a UV cleaner for 15 to 20 minutes.
[0036] (2) Preparation of perovskite precursor solution
[0037] Weigh 461 mg (1 mmol) of PbI2, add it to 1 mL of butylamine acetate solvent, place it on a 60°C hot plate and stir overnight to dissolve, and prepare a perovskite precursor solution with a concentration of 1 mol / L;
[0038] (3) Preparation of perovskite thin films
[0039] In an air environment, the ITO substrate in step (1) is heated to 80°C, and the perovskite precursor solution in step (2) is measured by a pipette and spin-coated on the ITO surface. The spin coater speed is set to 4000 rpm for 20 seconds, and then annealed at 100°C for 5 minutes to obtain a perovskite film layer.
[0040] (4) Preparation of top electrode
[0041] The substrate in step (3) is placed in a vacuum evaporation device, and a strip array Al electrode with a width of 2.5 mm and a thickness of 100 nm is deposited on the surface of the perovskite film using a vacuum evaporation method and a mask plate to obtain a device with a cross structure.
[0042] The two-dimensional perovskite resistive random access memory described in this embodiment is a stacked structure, such as Figure 1 It consists of glass substrate, bottom electrode ITO, two-dimensional perovskite BA2PbI x (Ac) 4-x The resistive layer and the top electrode Al are composed. The bottom electrode is transparent conductive glass ITO, with a thickness of 200 nm, a strip shape and a width of 2 mm; the resistive layer material is BA2PbI x (Ac) 4-x The resistive layer has a thickness of 300 nm, a rectangular shape, and a side length of 12 mm; the top electrode is Al, has a thickness of 100 nm, and is in the shape of a strip array with a width of 2.5 mm.
[0043] The performance of the memory was tested using a precision source meter Keithley 2400. It can be seen that the device is a typical non-volatile memory that can store data at a relatively low voltage and has an on / off ratio of 10. 4 , excellent performance, the IV relationship curve of the memory is as follows Figure 4 As shown. When the forward voltage is applied in the range of 0-0.7 V, the device first presents a "high resistance state". When the voltage reaches 0.7 V, the current rises rapidly, indicating that the device changes from a "high resistance state" to a "low resistance state", which is the "write" process of the memory. Subsequently, when the voltage is scanned from 2 V to -2 V, the device changes to a "high resistance state" at a voltage of -0.3 V, realizing a non-volatile resistive memory that can be read and written repeatedly.
[0044] In order to study the differences in the film morphology and crystal structure formed by PbI2 solutions with different concentrations, we determined three different concentrations of PbI2 solutions: 0.3 mol / L, 0.7 mol / L, and 1.3 mol / L, and studied the morphology and crystal structure of the films respectively.
[0045] Embodiment 2:
[0046] (1) Cleaning ITO
[0047] First, ultrasonicate the ITO conductive glass in deionized water, acetone, and alcohol for 30 minutes, and then irradiate the ITO surface with ultraviolet light in a UV cleaner for 15 to 20 minutes.
[0048] (2) Preparation of perovskite precursor solution
[0049] Weigh 138.3 mg (0.3 mmol) of PbI2, add it to 1 mL of butylamine acetate solvent, place it on a 60°C hot plate and stir overnight to dissolve, and prepare a perovskite precursor solution with a concentration of 0.3 mol / L;
[0050] (3) Preparation of perovskite thin films
[0051] In an air environment, the ITO substrate in step (1) is heated to 80°C, and the perovskite precursor solution in step (2) is measured using a pipette and spin-coated on the ITO surface. The spin coater speed is set to 4000 rpm for 20 seconds, and then annealed at 100°C for 5 minutes to obtain a perovskite film layer.
[0052] Embodiment 3:
[0053] (1) Cleaning ITO
[0054] First, ultrasonicate the ITO conductive glass in deionized water, acetone, and alcohol for 30 minutes, and then irradiate the ITO surface with ultraviolet light in a UV cleaner for 15 to 20 minutes.
[0055] (2) Preparation of perovskite precursor solution
[0056] Weigh 322.7 mg (0.7 mmol) of PbI2, add it to 1 mL of butylamine acetate solvent, place it on a 60°C hot plate and stir overnight to dissolve, and prepare a perovskite precursor solution with a concentration of 0.7 mol / L.
[0057] (3) Preparation of perovskite thin films
[0058] In an air environment, the ITO substrate in step (1) is heated to 80°C, and the perovskite precursor solution in step (2) is measured using a pipette and spin-coated on the ITO surface. The spin coater speed is set to 4000 rpm for 20 seconds, and then annealed at 100°C for 5 minutes to obtain a perovskite film layer.
[0059] Embodiment 4:
[0060] (1) Cleaning ITO
[0061] First, ultrasonicate the ITO conductive glass in deionized water, acetone, and alcohol for 30 minutes, and then irradiate the ITO surface with ultraviolet light in a UV cleaner for 15 to 20 minutes.
[0062] (2) Preparation of perovskite precursor solution
[0063] Weigh 599.3 mg (1.3 mmol) of PbI2, add it to 1 mL of butylamine acetate solvent, place it on a 60°C hot plate and stir overnight to dissolve, and prepare a perovskite precursor solution with a concentration of 1.3 mol / L;
[0064] (3) Preparation of perovskite thin films
[0065] In an air environment, the ITO substrate in step (1) is heated to 80°C, and the perovskite precursor solution in step (2) is measured using a pipette and spin-coated on the ITO surface. The spin coater speed is set to 4000 rpm for 20 seconds, and then annealed at 100°C for 5 minutes to obtain a perovskite film layer.
[0066] The surface morphology (SEM) of the perovskite film of Example 1-4 is shown in Figure 2 As shown. The film coverage formed by low concentration of PbI2 is low, and there are a large number of relatively large pinholes, and the film morphology is poor. As the concentration of PbI2 increases, the overall grain size increases, the pinholes also decrease significantly, and the film coverage gradually increases. At a concentration of 1.3 mol / L, a large amount of PbI2 is instantly precipitated during the annealing process of the film, forming large grains that are disorderly piled up, resulting in an uneven film surface. The perovskite solution with a concentration of 1 mol / L in Example 1 exhibits the best film morphology.
[0067] The X-ray diffraction (XRD) patterns of the perovskite films of Examples 1-4 are as follows: Figure 3 As shown. For films with different concentrations, the PbI2 peak is dominant. It is worth noting that as the PbI2 concentration increases, the film shows a gradually enhanced diffraction peak at 2θ≈8.3°. This peak has a certain displacement compared to the traditional two-dimensional BA2PbI4 perovskite diffraction peak. The residual Ac in the film - Entered the PbI2 lattice to form the structure BA2PbI x (Ac) 4-x Perovskite. In the precursor solution, butylamine acetate is wrapped around PbI2, where Ac - It is very easy to form a strong Pb-O bond with PbI2, which can promote the dissolution of PbI2 to form a relatively stable precursor solution. Under annealing conditions, the nucleation process of perovskite is - Pb 2+ Formation of [PbI6] 4- Octahedron. The remaining Ac in the film - Ionic radius and I - are of the same order of magnitude, so Ac - Participate in the formation of [PbI x (Ac - ) 6-x ] 4- , and then form BA2PbI x (Ac) 4-x Perovskite.
[0068] Comparative Example 1:
[0069] (1) Cleaning ITO
[0070] First, ultrasonicate the ITO conductive glass in deionized water, acetone, and alcohol for 30 minutes, and then irradiate the ITO surface with ultraviolet light in a UV cleaner for 15 to 20 minutes.
[0071] (2) Preparation of perovskite precursor solution
[0072] Weigh 461 mg (1 mmol) of PbI2 and 402.1 mg (2 mmol) of butylamine iodide and add them to 1 mL of butylamine acetate solvent. Place the mixture on a 60°C hot plate and stir overnight to dissolve the mixture to prepare a 1 mol / L perovskite precursor solution.
[0073] (3) Preparation of perovskite thin films
[0074] In a water-free and oxygen-free environment of a glove box, use a pipette to measure the perovskite precursor solution in step (2) and spin-coat it on the ITO surface in step (1), the spin coater speed is set to 3000-4000 rpm, the time is 20 seconds, and then annealed at 100-120° C. for 10 minutes to obtain a perovskite thin film layer;
[0075] (4) Preparation of top electrode
[0076] The substrate in step (3) is placed in a vacuum evaporation device, and a strip array Al electrode with a width of 2.5 mm and a thickness of 100 nm is deposited on the surface of the perovskite film using a vacuum evaporation method and a mask plate to obtain a device with a cross structure.
[0077] Comparative Example 1 is a method for preparing a two-dimensional perovskite BA2PbI4 thin film using two precursors. The performance of the above memory is tested using a precision source meter Keithley 2400. The IV relationship curve of the memory is as follows: Figure 5 As shown, it can be seen that within the voltage scanning range of -2 V to 2 V, the switching ratio of the device is extremely small, much less than 10.
[0078] Comparative Example 2:
[0079] (1) Cleaning ITO
[0080] First, ultrasonicate the ITO conductive glass in deionized water, acetone, and alcohol for 30 minutes, and then irradiate the ITO surface with ultraviolet light in a UV cleaner for 15 to 20 minutes.
[0081] (2) Preparation of perovskite precursor solution
[0082] Weigh 461 mg (1 mmol) of PbI2 and 402.1 mg (2 mmol) of butylamine iodide and add them to 1 mL of a mixed solvent (DMF:DMSO = 4:1). Place the mixture on a 60°C hot plate and stir overnight to dissolve to prepare a perovskite precursor solution with a concentration of 1 mol / L.
[0083] (3) Preparation of perovskite thin films
[0084] In a water-free and oxygen-free environment of a glove box, use a pipette to measure the perovskite precursor solution in step (2) and spin-coat it on the ITO surface in step (1), the spin coater speed is set to 3000-4000 rpm, the time is 20 seconds, and then annealed at 100-120° C. for 10 minutes to obtain a perovskite thin film layer;
[0085] (4) Preparation of top electrode
[0086] The substrate in step (3) is placed in a vacuum evaporation device, and a strip array Al electrode with a width of 2.5 mm and a thickness of 100 nm is deposited on the surface of the perovskite film using a vacuum evaporation method and a mask plate to obtain a device with a cross structure.
[0087] Comparative Example 2 is a conventional method for preparing a two-dimensional perovskite BA2PbI4 thin film. The performance of the memory device is tested using a precision source meter Keithley 2400. The IV relationship curve of the memory device is shown in FIG. Figure 6 As shown, it can be seen that within the voltage scanning range of -2 V to 2 V, the switching ratio of the device is extremely small, much less than 10.
[0088] Comparative Example 3:
[0089] (1) Cleaning ITO
[0090] First, ultrasonicate the ITO conductive glass in deionized water, acetone, and alcohol for 30 minutes, and then irradiate the ITO surface with ultraviolet light in a UV cleaner for 15 to 20 minutes.
[0091] (2) Preparation of perovskite precursor solution
[0092] Weigh 230.5 mg (0.5 mmol) of PbI2 and add it to 1 mL of mixed solvent (DMF:DMSO = 4:1). Place it on a 60°C hot plate and stir overnight to dissolve.
[0093] (3) Preparation of thin films
[0094] In a water-free and oxygen-free environment of a glove box, use a pipette to measure the solution in step (2) and spin-coat it on the ITO surface in step (1), the spin coater speed is set to 3000-4000 rpm, the time is 20 s, and then annealed at 100-120° C. for 10 min to obtain a thin film layer;
[0095] (4) Preparation of top electrode
[0096] The substrate in step (3) is placed in a vacuum evaporation device, and a strip array Al electrode with a width of 2.5 mm and a thickness of 100 nm is deposited on the surface of the film using a vacuum evaporation method and a mask plate to obtain a device with a cross structure.
[0097] Comparative Example 3 is the preparation of a two-dimensional perovskite film using a traditional solvent (DMF:DMSO = 4:1). The performance of the above memory is tested using a precision source meter Keithley 2400. The IV relationship curve of the memory is as follows: Figure 7 As shown, it can be seen that after the device undergoes the initialization forming process, the device exhibits an extremely low switching ratio in the voltage scanning range of -2 V ~ 2 V.
[0098] Therefore, the method of the embodiment of the present invention prepares the two-dimensional perovskite film, which not only simplifies the preparation process of the two-dimensional perovskite film, but also realizes a resistive random access memory with a high switching ratio. This preparation method is simple and highly controllable, providing technical support for the further commercialization of resistive random access memory.
Claims
1. A method for preparing a two-dimensional perovskite resistive memory device based on an ionic liquid solvent, characterized in that: The invention comprises a glass substrate, on which are arranged a bottom electrode, a two-dimensional perovskite resistive switching layer and a top electrode in sequence; the bottom electrode is transparent ITO; the resistive switching layer material is BA2PbI x (Ac) 4-x Thin film; the top electrode is Al; The preparation steps are as follows: (1) Cleaning ITO First, ultrasonicate the ITO conductive glass in deionized water, acetone, and alcohol for 30 minutes, and then irradiate the ITO surface with ultraviolet light in a UV cleaner for 15 to 20 minutes. (2) Preparation of perovskite precursor solution Weigh 461 mg (1 mmol) of PbI2, add it to 1 mL of butylamine acetate solvent, place it on a 60°C hot plate and stir overnight to dissolve, and prepare a perovskite precursor solution with a concentration of 1 mol / L; (3) Preparation of perovskite thin films In an air environment, the ITO substrate in step (1) is heated to 80-90°C, and the perovskite precursor solution in step (2) is measured by a pipette and spin-coated on the ITO surface, the spin coater speed is set to 3000-4000 rpm, the time is 20s, and then annealed at 90-100°C for 5 min to obtain a perovskite film layer; (4) Preparation of top electrode The substrate in step (3) is placed in a vacuum evaporation device, and a strip array Al electrode with a width of 2.5 mm and a thickness of 100 nm is deposited on the surface of the perovskite film using a vacuum evaporation method and a mask plate to obtain a device with a cross structure.
2. The method for preparing a two-dimensional perovskite resistive memory device based on an ionic liquid solvent according to claim 1, characterized in that: The bottom electrode is ITO with a thickness of 200 nm, a strip array shape and a width of 2 mm; the resistive layer material is BA2PbI x (Ac) 4-x The resistive layer has a thickness of 300 to 350 nm, a rectangular shape, and a side length of 12 mm; the top electrode is Al, has a thickness of 100 nm, and is in the shape of a strip array with a width of 2.5 mm.
3. The method for preparing a two-dimensional perovskite resistive memory device based on an ionic liquid solvent according to claim 1, characterized in that: In step (3), the spin coater speed is set to 4000 rpm, and the resistive switching layer BA2PbI x (Ac) 4-x The film thickness is 300 nm.
4. The method for preparing a two-dimensional perovskite resistive memory device based on an ionic liquid solvent according to claim 1, characterized in that: In step (3), the spin coater speed is set to 4000 rpm, and the resistive switching layer BA2PbI x (Ac) 4-x The film thickness is 300 nm, wherein in step (4), a strip array Al electrode with a width of 2.5 mm is deposited on the surface of the perovskite film using a vacuum evaporation method and a mask plate.
5. A non-volatile resistive random access memory based on an ionic liquid solvent and capable of being repeatedly read and written prepared according to any one of the methods of claims 1 to 4.
6. The application of the rewritable non-volatile resistive random access memory based on ionic liquid solvent according to claim 5, characterized in that: The device is a non-volatile memory that can store data at a lower voltage and has an on / off ratio of 10. 4 .
Citation Information
Patent Citations
Two-dimensional halogen perovskite resistive random access memory and preparation method thereof
CN115332438A